2013 IEEE 63rd Electronic Components and Technology Conference 2013
DOI: 10.1109/ectc.2013.6575674
|View full text |Cite
|
Sign up to set email alerts
|

Power comparison of 2D, 3D and 2.5D interconnect solutions and power optimization of interposer interconnects

Abstract: This paper compares the power efficiency of multiple 2D, 2.5D and 3D interconnect scenarios, specifically DDR3 with PCB, DDR3 with interposers, LPDDR2(3) with POP, wide I/Os with through-silicon vias (TSVs) and interposers and 32 nm technology CMOS drivers with TSVs and on-chip wires. It was found that DDR3 with PCB is the lowest power efficiency (15.65 mW/Gbps) and custom designed CMOS drivers optimized for the 2.5D and 3D give the highest power efficiency (0.23mW/Gbps). Optimization of a Back End of the Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…The data presented in Figure 3 (taken from [2]) compares the power efficiency of a subset of these, and other, interface standards. This data highlights the significant power efficiency advantage of 3D technologies over conventionally packaged solutions.…”
Section: B Memory Bandwidth and Powermentioning
confidence: 99%
“…The data presented in Figure 3 (taken from [2]) compares the power efficiency of a subset of these, and other, interface standards. This data highlights the significant power efficiency advantage of 3D technologies over conventionally packaged solutions.…”
Section: B Memory Bandwidth and Powermentioning
confidence: 99%
“…We demonstrate our methodology by integrating Wide I/O memory [11] and multi-partition logics on a 2.5D/3D package interfaced with a monolithic SOC flip chip die realized on a multi-layer organic build-up substrate. The flip chip SOC package is subsequently interfaced with a rigid silicon interposer package, a DDR4 package, a connector and a wirdebonded BGA laminate package on the PCB (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work has shown that interconnects on a silicon interposer have high power efficiency for smaller pitch due to small ground capacitance [4]. However, other important design objectives have not been investigated in [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, other important design objectives have not been investigated in [4]. In addition, other materials, such as glass with potential performance benefits need to be explored [2].…”
Section: Introductionmentioning
confidence: 99%